Immigrants’ consumption choices: evidence from Korea’s food service industry - Yinhua Quan; Youngjune Kim; Jeongbin Im (Humanities & Social Sciences Communications)
Abstract This study addresses three key questions: Are immigrants positively associated with the food service industry? Which restaurant categories are they linked to, and why? These questions have rarely been explored within a unified analytical framework. This study examines them in the context of South Korea—a traditionally monoethnic nation that has experienced significant immigration growth since the 1988 Seoul Olympics. This trend suggests a potential connection between the growing immigrant population, the diversification of culinary culture, and the transformation of South Korea’s food service landscape. By using a 10-year panel dataset covering all districts of South Korea, we estimate the effects of immigration on the number of restaurants. We find that immigrants do not significantly affect the overall number of restaurants or foreign food establishments. Instead, they are more strongly associated with low-cost, time-efficient restaurant categories, whereas native Koreans exhibit broader preferences across a wider range of restaurant types.